1997
DOI: 10.1039/np9971400221
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the gibberellin plant hormones

Abstract: Turnip Pumpkin Marrow Cucumber 'Jacaranda do cerrado" Barley Tomato Wild cucumber Rice Spruce Runner bean Pea French bean Castor bean Garden radish Sorghum Chocho Bay willow Spinach Wheat Maize Apple Arabidopsis thaliana Brassica rapa Cucurbita maxima Cucurbita pep0 Cucumis sativus Dalbergia dolichopetala Hordeum vulgare Lycopersicon esculentum Malus domestica Marah macrocarpus Oryza sativa Picea abies Phaseolus coccineus Pisum sativum Phaseolus vulgaris Ricinus communis Raphunus sativus Sorghum bicolor Sechiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
77
0
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(81 citation statements)
references
References 173 publications
1
77
0
3
Order By: Relevance
“…In our experiments, the wild-type strain converted GA 12 to nonpolar products, consistent with the results of Bearder et al (28), who found that GA 12 is metabolized mainly to the non-3␤-hydroxylated GA, GA 9 . The small amount of GA 3 formed from GA 12 may be the result of the low rate of 3␤-hydroxylation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our experiments, the wild-type strain converted GA 12 to nonpolar products, consistent with the results of Bearder et al (28), who found that GA 12 is metabolized mainly to the non-3␤-hydroxylated GA, GA 9 . The small amount of GA 3 formed from GA 12 may be the result of the low rate of 3␤-hydroxylation.…”
Section: Discussionmentioning
confidence: 99%
“…1) are identical for plants and fungi, but the pathways diverge thereafter. The major end product of the pathway in G. fujikuroi is gibberellic acid (GA 3 ), which is a minor GA component in most plant species.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In line with current nomenclature for GA biosynthesis enzymes and the corresponding genes (10), we will refer to GA3 as AtKO1. The genes encoding the enzymes catalyzing the conversion of KA to ent-7␣-hydroxykaurenoic acid (7OH-KA) and 7OH-KA to GA 12 -aldehyde have not been isolated, but it is known that these reactions are likely to be catalyzed by cytochrome P450s requiring O 2 and NADPH for activity (11).…”
mentioning
confidence: 99%
“…Gibberellin transport might be governed by processes other than simple pH-dependent diffusion across the membrane (Nour & Rubery, 1984). Rapid metabolism and inactivation of GA taken up by the cell might also have occurred (Hedden & Kamiya, 1997 ;MacMillan, 1997). In addition, physiological effects of altered extracellular pH might have been superimposed on the response to changed GA permeability (Bush & Jones, 1988).…”
Section:       mentioning
confidence: 99%